ECONOMIC LOSS ANALYSIS DUE TO THE FAILURE OF PAMUKKULU DAM IN TAKALAR, SOUTH SULAWESI, INDONESIA - Widyaningtias; Ibnu Malik, Muhamad Zaky; Adityawan, Mohammad Bagus; Nurganah Chaidar, Ana; Zahira Rustiawan, Irfani (GEOMATE Journal, 2025)
Every dam has the potential to fail due to disasters like earthquakes or other unforeseen events. Dam failures caused by extreme weather are particularly difficult to predict, which can lead to casualties and significant economic losses. This study aims to analyze the potential economic losses resulting from the failure of the Pamukkulu Dam, located in Takalar Regency, South Sulawesi Province, Indonesia. Extreme weather is considered the primary factor causing failure, projecting the worst-case scenario. The Probable Maximum Precipitation (PMP), the maximum rainfall that can occur in an area, was calculated using the Hershfield method, while the inflow discharge analyzed was the Probable Maximum Flood (PMF). The Synthetic Unit Hydrograph (SUH) was selected using the Creager method, resulting in ITB-1b being chosen. Dam failure and flood inundation simulations were conducted using HEC-RAS 6.6 software, based on two failure scenarios: overtopping and piping. The overtopping scenario produced the highest peak discharge, reaching 33,247.67 m³/s, which was used to calculate economic losses for the most extreme condition. The simulation results showed that the inundated area due to dam failure under the overtopping scenario reached 110.79 km². Economic loss analysis was performed using the ECLAC method, based on the inundation area, land cover types, flood depth, combined with unit replacement values and damage factors. The estimated economic loss from the Pamukkulu Dam failure under the overtopping scenario is approximately IDR 1.12 trillion. The findings of this study are expected to support post-disaster recovery efforts and serve as a reference for developing flood risk management strategies.